A Quasi-Experimental Study on the Effects of Community versus Custodial Sanctions in Youth Justice. (April 2023) - Koops-Geuze, Gwendolyn J.; Wermink, Hilde T.; Weerman, Frank M.
Although community sanctions have become a popular alternative to custodial sanctions in youth justice, primary questions about the recidivism effects of community sanctions remain unanswered. The current study aims to fill this gap through a quasi-experimental analysis of 2-year recidivism differences between 4, 425 youth subject to community sanctions versus custodial sanctions in the Netherlands in 2015 and 2016. Recidivism was analyzed in terms of overall, serious, and very serious recidivism for the full sample, a low risk subsample, and a medium-high risk subsample. Findings indicate that youth subject to community sanctions are less likely to recidivate overall, and less like likely to recidivate seriously than youth subject to custodial sanctions. Community sanctions were found to be particularly beneficial for preventing very serious recidivism among low risk youth. Additionally, it was found that medium-high risk youth subject to community sanctions are less likely to recidivate overall, and less seriously than medium-high risk youth subject to custodial sanctions. Implications of these findings for future research and practice are discussed.